نظم المعلومات التسويقية ومساهمتها في تطوير إدارة العلاقة مع الزبائن - شيخة مبروك, العروسي (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
الملخص: تهدف الدراسة إلى كشف وتحديد طبيعة علاقة الارتباط وقياس الأثر المحدث من خلال تطبيق أبعاد نظام المعلومات التسويقية (نظام السجلات الداخلية، نظام الاستخبارات التسويقية، نظام بحوث التسويق، نظام دعم القرارات التسويقية) على تطوير إدارة العلاقة مع الزبون في القطاع المصرفي الجزائري على اعتباره قطاعًا حيويًا. ولتحقيق أهداف الدراسة اُعتمد في الجانب النظري على المعلومات المستقاة من الكتب والدراسات، إضافة للأبحاث السابقة العربية منها والأجنبية، فيما شملت الدراسة التطبيقية تصميم استبيان كأداة رئيسية للدراسة، بهدف جمع البيانات من موظفي القطاع المصرفي المعنيين بالموضوع المعالج، حيث تم توزيع (377) استبيانًا، ليتم استرداد (337) استبيانًا، وبعد مراجعة وتدقيق الاستمارات المستردة وجد منها (316) استبيانًا فقط صالحا للتحليل. ومن أجل تسهيل عملية تحليل ومناقشة النتائج تم الاستعانة ببرنامج الحزمة الإحصائية للعلوم الاجتماعية (SPSS 25) لمعالجة البيانات واستخراج نتائج الدراسة. وقد أثبتت النتائج التطبيقية أن نظام المعلومات التسويقية بمكوناته (نظام السجلات الداخلية، نظام الاستخبارات التسويقية، نظام البحوث التسويقية، نظام دعم القرارات التسويقية) له تأثير إيجابي ومساهمة قوية في تطوير إدارة العلاقة مع الزبون في المؤسسات محل الدراسة، ومن خلال نتائج الدراسة قدم الطالب مجموعةً من التوصيات والمقترحات. Abstract: The study aims to reveal and determine the nature of the correlation relationship and measure the impact created by applying the dimensions of the marketing information system (internal records system, marketing intelligence system, marketing research system, marketing decision support system) on the development of customer relationship management in the Algerian banking sector as a vital sector. In order to achieve the objectives of the study, the theoretical side relied on information drawn from books and studies, in addition to previous Arabic and foreign research, while the applied study included designing a questionnaire as a main tool for the study, with the aim of collecting data from banking sector employees concerned with the subject dealt with, where (377) questionnaires were distributed, (337) questionnaires were retrieved, and after reviewing and checking the retrieved forms, only (316) questionnaires were found valid for analysis. In order to facilitate the process of analyzing and discussing the results, the Statistical Package for Social Sciences (SPSS 25) program was used to process the data and extract the results of the study. The applied results have proven that the marketing information system with its components (internal records system, marketing intelligence system, marketing research system, marketing decision support system) has a positive impact and a strong contribution to the development of customer relationship management in the institutions under study, And through the results of the study, the student presented a set of recommendations and proposals.
- دراسة حالة القطاع المصرفي الجزائري -
أطروحة دكتوراه تخصص: تسويق ونظم المعلومات في العلوم الاقتصادية و التحارية وعلوم التسيير
Keywords: نظم المعلومات التسويقية، زبون، إدارة العلاقة مع الزبون، مصارف جزائرية.; Marketing information system, Customer, Customer relationship management Algerian bank.